BUBBLE CPAP NON-INVASIVE VENTILATION IN TREATMENT OF ATELECTASIS AFTER CARDIAC SURGERY: CASE REPORТ - Hristina Mandzukovskа (Институт за јавно здравје на Република Македонија = Institute of public health of Republic of Macedonia, 2018)
Bubble CPAP is a simple, safe, non-invasive and cost effective method of delivering respiratory support to premature and term neonates. Application of Continuous Positive Airway Pressure (CPAP) in neonates and infants with respiratory distress is associated with reduction of respiratory failure, lung complications and mortality. Case report: We present a case of an infant with congenital heart defect - coartation of the aorta. Cardiac surgery was done at the infant’s two weeks age. Deterioration of the general condition was observed in the postoperative period along with respiratory insufficiency. Extubation efforts were unsuccessful due to the presence of atelectasis. After bubble CPAP was placed, the atelectasis completely disappeared. Conclusion: The administration of bubble CPAP is as effective as the other forms of non-invasive ventilation, and can decrease the length of hospital stay, which indicates that bubble CPAP could be an optimal alternative in treatment of respiratory failure.